Do Government Policies that Promote Competition Encourage— or Discourage—New Product and Process Development In Low and Middle-Income Countries? - Clarke, George R. G. (World Bank, Washington, DC, 2012)
Previous work has shown that firms in low and middle-income countries in Eastern Europe and Central Asia that feel greater pressure to innovate from their competitors are more likely to introduce new products and services than firms that do not feel pressure (Carlin and others 2001; World Bank 2004). However, competition also appears to affect innovation in other ways. In particular, firms in these countries that face greater price competition appear to be less likely to innovate than other firms (Carlin and others 2001). The author assesses how competition and trade policy affect these different aspects of competition and, consequently, assesses their net impact on innovation. He finds that reducing tariffs and enacting and enforcing competition laws modestly increases both the pressure that firms feel regarding innovation and the level of price competition in the domestic economy. The net impact that lower tariffs have on new product and process development appears to be negative but small-for the most part the opposing effects cancel out. In contrast, stricter competition laws and better enforcement of those laws appear to increase the likelihood of new product and process development, especially when competition is treated as endogenous to innovation.